How social factors relate to arthritis risk in Chinese older adults: population-based evidence - Xu, Liang; Fu, Jiangning; Zhai, Boyu; Li, Jing (Frontiers in Public Health, 2025)
BackgroundArthritis prevalence is rising among older adults globally, including in China, where the aging population is increasing. Social factors, such as social networks, participation, and support, have been associated with inflammation response. However, limited research has explored how these factors affect arthritis in Chinese older adults. This study aimed to examine the association between social factors and arthritis risk using data from the 2017–2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS).MethodsA total of 15,854 individuals aged 60 and above were included. Arthritis status was assessed through self-reports, and key social factors—social network size, social participation, and social support were measured. Binary logistic regression models were used to analyze associations, adjusting for demographic and health-related variables.ResultsA larger social network was associated with a lower risk of arthritis (OR = 0.963, p = 0.015). Higher social participation, however, was associated with a higher risk (OR = 1.027, p = 0.007). Emotional support demonstrated a protective effect (OR = 0.963, p = 0.006), while instrumental support showed no significant impact. A significant interaction between social participation and emotional support (p = 0.008) indicated that emotional support mitigates the elevated risk of arthritis associated with high social participation.ConclusionSocial factors play a crucial role in arthritis risk among older adults. While broader social networks and emotional support appear beneficial, increased social participation may contribute to higher risk. These findings highlight the need for tailored interventions to promote healthy aging.